Narrating the "Asylum Story": Between Literary and Legal Storytelling. Issue 3 (3rd April 2017) - Woolley, Agnes
Abstract : In 2014 the United Nations High Commission for Refugees reported that the number of forcibly displaced people worldwide had exceeded 50 million for the first time since the Second World War. The entanglement of literary and legal technologies in the asylum decision-making process as it operates today in legal, advocacy and creative circles excludes asylum seekers from incorporation as rights-bearing individuals if they do not conform to a particular narrative of persecution. In a moment of anxiety over "the meaning and scope of citizenship" comparable to that of the postwar period – and facing a refugee crisis of a similar scale – an investigation of the means by which asylum protection is constituted by and enacted through narrative forms is long overdue. This essay analyses the procedural characteristics of the asylum decision-making process, which produces what I call the "asylum story": an idealized version of refugeehood on which the civic incorporation of the asylum seeker depends and which circulates in a narrative economy that sets the terms for the enunciation of refugee experience. It considers how the notion of a discoverable truth has inflected literary engagements with asylum, which are beset by the same anxieties around veracity and authenticity endemic to the legal process of decision-making on asylum, and ends with an analysis of Chimamanda Ngozi Adichie's short story "The American Embassy" from her 2009 collection The Thing Around Your Neck . I argue that the story exposes the narrative instabilities of the asylum determination process, highlighting the ways in which those international institutions designed to protect human rights continue to be deeply implicated in regimes of truth which regulate upon whom they may be conferred.